2012
DOI: 10.1200/jco.2012.30.15_suppl.9005
|View full text |Cite
|
Sign up to set email alerts
|

ZOOM: A prospective, randomized trial of zoledronic acid (ZOL; q 4 wk vs q 12 wk) for long-term treatment in patients with bone-metastatic breast cancer (BC) after 1 yr of standard ZOL treatment.

Abstract: 9005 Background: ZOL (4 mg q 4 wk) is an established therapy for reducing the risk of debilitating skeletal-related events (SREs) in patients (pts) with bone metastases (mets) from BC. As BC treatments continue to improve pt survival, long-term SRE-reduction is increasingly important, and evaluation of modified ZOL dosing to retain efficacy with reduced adverse events (AEs) is warranted. Methods: ZOOM, a phase III prospective, randomized, open-label, multicenter study, assessed the safety and efficacy of quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…The randomized phase III ZOOM trial assessed the safety and efficacy of switching to quarterly zoledronic acid versus continuing with monthly in patients (n=425) with bone metastases from breast cancer who received prior zoledronic acid treatment. 264 Safety analyses showed that zoledronic acid was well tolerated in the long term, and renal adverse events were seen in similar proportions of patients in both arms. This study was underpowered to confirm noninferiority between the arms, although rates of SREs were similar.…”
Section: Treatment Of Bone Metastases Pharmacologic Options For Patiementioning
confidence: 91%
See 1 more Smart Citation
“…The randomized phase III ZOOM trial assessed the safety and efficacy of switching to quarterly zoledronic acid versus continuing with monthly in patients (n=425) with bone metastases from breast cancer who received prior zoledronic acid treatment. 264 Safety analyses showed that zoledronic acid was well tolerated in the long term, and renal adverse events were seen in similar proportions of patients in both arms. This study was underpowered to confirm noninferiority between the arms, although rates of SREs were similar.…”
Section: Treatment Of Bone Metastases Pharmacologic Options For Patiementioning
confidence: 91%
“…This study was underpowered to confirm noninferiority between the arms, although rates of SREs were similar. 264 Similarly, the ongoing OPTIMIZE 2 trial is studying patients with breast cancer with bone metastases who have received prior monthly zoledronic acid. OPTIMIZE 2 patients are randomized in a double-blind fashion to continue monthly dosing for an additional year versus changing dosing intervals to every 3 months (ClinicalTrials.gov identifier: NCT00320710).…”
Section: Treatment Of Bone Metastases Pharmacologic Options For Patiementioning
confidence: 99%
“…There is considerable interest in optimizing the frequency of administration of bone-targeted agents as the current “one size fits all” approach is likely inefficient, expensive, and there is reason to believe that some patients may achieve equivalent benefit and improved safety with less frequent treatment administration. The results of the two published trials, assessing reduced frequencies of administration of these agents, would suggest there is still a need for larger definitive studies [12] , [13] . In addition, we are not aware of any similar studies planned for prostate cancer where again the benefits of bone-targeted agents in reducing SREs are likely even more modest than that seen in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results do however confirm that physicians are very interested in de-escalation trials and that they would consider de-escalating therapy from every 3–4 weeks to 3 monthly therapy and entering patients on such a study at anytime from 3 months to 2 years after starting treatment. However, physicians do want the primary study endpoint to be SRE [11] and not biomarker studies using biomarkers of bone turnover as a surrogate for skeletal related event risk [12] . Ultimately the results from our survey confirms that trials exploring de-escalated use of bone targeted agents are wanted for both breast and prostate cancer and that ultimately there will remain a need for further very large randomised trials with skeletal related events as the primary endpoint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation